2016
DOI: 10.1016/s1474-4422(16)30236-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation and comparison of imaging-based scores for prediction of early stroke risk after transient ischaemic attack: a pooled analysis of individual-patient data from cohort studies

Abstract: Health Research Board of Ireland, Irish Heart Foundation, Irish Health Service Executive, Irish National Lottery, National Medical Research Council of Singapore, Swiss National Science Foundation, Bangerter-Rhyner Foundation, Swiss National Science Foundation, Swisslife Jubiläumsstiftung for Medical Research, Swiss Neurological Society, Fondazione Dr Ettore Balli (Switzerland), Clinical Trial Unit of University of Bern, South Korea's Ministry for Health, Welfare, and Family Affairs, UK Wellcome Trust, Wolfson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 30 publications
4
44
1
Order By: Relevance
“…The distribution of ABCD 2 score was consistent with that observed in other large cohort studies [18, 26]. A large proportion of TIA patients had a high risk of recurrence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The distribution of ABCD 2 score was consistent with that observed in other large cohort studies [18, 26]. A large proportion of TIA patients had a high risk of recurrence.…”
Section: Discussionsupporting
confidence: 89%
“…Only 23% of TIA patients had a brain MRI, and among these, 15.5% had an infarct lesion corresponding to the event. This rate is lower than that reported in a recently published pooled analysis of TIA cohort studies (31%) [18], probably because in our setting, MRI was performed from hours to days after symptom onset, and it has been shown that the probability of detecting a lesion on MRI depends on the timing of the imaging procedure [19, 20]. It is noteworthy that the detection of an infarct lesion with CT scan was even lower (2.4% of patients).…”
Section: Discussioncontrasting
confidence: 70%
“…Results showed that high ABCD score indicates high incidence of stroke within 30 d. ABCD score reached 0-2, 3, 4, 5, and 6 with risks of stroke reaching 0%, 3.5%, 7.6%, 21.3% and 31.3% respectively; at the same time, ABCD score of 5-6 points within 30 d stroke risk is eight times higher than that of ABCD score of 4 points or less. 8,9 The study suggests good clinical use of this score to predict reliability of the risk of stroke after TIA. ABCD score can identify high risk of stroke patients at an early period.…”
Section: Abcd Scorementioning
confidence: 88%
“…8 ABCD score of 6points (approximately 30% within 7d stroke incidence) in the acute phase must be observed in hospital settings. In the event of stroke, clinicians can timely apply thrombolysis therapy.…”
Section: Abcd Scorementioning
confidence: 99%
See 1 more Smart Citation